Hodonyms of Subotica downtown as an evidence of city’s multiculturalism - David, Jaroslav (Geographical names in physical space, 2016)
Hodonyms function as symbols and convey information about relations between the inhabitants of the city. Considered as signs, they stigmatize space and, by references to different cultures, they reflect the demographic structure, in particular, the ethnic one. The article attempts to classify names of streets, squares and parks according to their references to the different cultures. The analysis was conducted on the example of the center of Subotica, a multicultural city in Serbia, near the border with Hungary. The next step was to present the phenomena on maps, which was done for three historical periods: the interwar, the Communist era and current state. The first two are based on maps from 1928 and 1968, and the current one is based on field research curried out in September 2011. The information obtained in this way was compared to the census results of different periods, analyzing the relationship between demographic structure and the information stored in the hodonyms. The analysis confirmed the possibility of using this method in terms of synchronic and diachronic viewpoint.